Macular Telangiectasia Type 2 With Spontaneous Resolution of Intraretinal/Sub-Internal Limiting Membrane Hemorrhage in the Absence of Neovascularization. (November 2017) - Chandra, Varun; Merani, Rohan; Hunyor, Alex P.; Ho, I-Van; Gillies, Mark
Purpose: To describe a case of macular telangiectasia type 2 (MacTel) presenting with decreased vision due to intraretinal/sub-internal limiting membrane (ILM) hemorrhage in the absence of neovascularization. Method: Clinical examination and multimodal imaging were performed. Results: A 65-year-old female presented with blurred left vision, recording 20/160 in that eye. There was intraretinal hemorrhage at the left macula centrally, with sub-ILM hemorrhage superiorly and inferiorly. Optical coherence tomography (OCT) showed no evidence of subretinal neovascularization. Imaging of the right macula was consistent with MacTel. The blood spontaneously cleared and the left visual acuity gradually improved to 20/25 by 4 months. Fluorescein angiography confirmed MacTel, and once the hemorrhage resolved, both inner and outer retinal cavitation was identified on OCT of the left macula. The left best-corrected visual acuity remained at 20/25 at 2-year follow-up. Conclusion: Spontaneous resorption of hemorrhage was accompanied by visual improvement.